2002
DOI: 10.1111/j.1745-9133.2002.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effects of Arrest on Intimate Partner Violence: Research, Policy and Theory*

Abstract: Research Summary:This research addresses the limitations of prior analyses and reviews of five experiments testing for the specific deterrent effect of arrest on intimate partner violence by applying to individual level data consistent eligibility criteria, common independent and outcome measures, and appropriate statistical tests. Based on 4,032 cases involving adult males who assaulted their female intimate partners, multivariate regression analyses show consistent but modest reductions in subsequent offense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 38 publications
8
92
2
Order By: Relevance
“…The Minneapolis Domestic Violence experiment by Sherman and colleagues and the related Spousal Assault Replication Program (SARP) experiments have provided some evidence to support the deterrent effects of arrest for misdemeanor assaults (Berk, Campbell, Klap, & Western, 1992;Maxwell et al, 2002;Sherman & Berk, 1984a, 1984b. In a recent pooled reanalysis of the SARP data, Maxwell et al (2002) also found modest support for the preventive effects of arrest.…”
Section: The Role Of Law Enforcementmentioning
confidence: 95%
See 1 more Smart Citation
“…The Minneapolis Domestic Violence experiment by Sherman and colleagues and the related Spousal Assault Replication Program (SARP) experiments have provided some evidence to support the deterrent effects of arrest for misdemeanor assaults (Berk, Campbell, Klap, & Western, 1992;Maxwell et al, 2002;Sherman & Berk, 1984a, 1984b. In a recent pooled reanalysis of the SARP data, Maxwell et al (2002) also found modest support for the preventive effects of arrest.…”
Section: The Role Of Law Enforcementmentioning
confidence: 95%
“…The body of literature on police strategies for handling domestic violence incidents has grown in recent years and has sparked considerable policy debate (Maxwell, Garner, & Fagan, 2002). Fagan et al (1983) found that 55% of men who had experienced informal police mediation and separation following a domestic conflict reported no subsequent assaults (Fagan, 1989).…”
Section: The Role Of Law Enforcementmentioning
confidence: 99%
“…In addition, the district attorney's computer database was searched to determine whether the victim in the new incident was the same as the victim in the original incident. In keeping with common practice in the field (e.g., Davis et al, 2006b;Feder and Dugan 2002;Maxwell et al 2002), we included only instances involving the same victim and perpetrator. To reduce measurement error, we combined the CJA arrest reports and the police complaint data into one measure that captured the number of documented police recorded incidents (e.g., arrests or crime complaints) involving the defendant and victim at any time after the treatment was assigned.…”
Section: Data Collectionmentioning
confidence: 99%
“…Conclusions depended on how recidivism was measured. Thus, a later analysis that combined the data from five replication sites found a statistically significant effect suggesting deterrence if repeat abuse was measured by later spousal interviews but found no statistically significant relationship if police records were the measure of repeat offending (Maxwell et al 2001(Maxwell et al , 2002. Although the results from this global analysis suggested arrest might prevent abuse and was unlikely to increase it, from a policy standpoint, their implications are ambiguous.…”
Section: Wwwannualreviewsorg • Growing Up In Law and Societymentioning
confidence: 75%